2020
DOI: 10.1007/s10853-020-05513-6
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxylated boron nitride materials: from structures to functional applications

Abstract: Functionalization of boron nitride (BN) materials with hydroxyls has attracted great attention to accomplish better performances at micro- and nanoscale. BN surface hydroxylation, in fact, induces a change in properties and allows expanding the fields of application. In this review, we have summarized the state-of-the-art in developing hydroxylated bulk and nanoscale BN materials. The different synthesis routes to develop hydroxyl BN have been critically discussed. What emerges is the great variety of possible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 135 publications
(262 reference statements)
0
40
0
Order By: Relevance
“…h‐BN can be formed in a large variety of different nanostructures from 3D to 0D, such as monolayers, nanoribbons, nanotubes, nanodots, nanocages, and fullerene‐like molecules. [ 7,8 ] In particular, h‐BN can be easily exfoliated from bulk crystals down to few layers or deposited as monolayer using different methods. [ 9 ] h‐BN nanosheets have been obtained by developing both top‐down and bottom‐up routes even if controlling the number of layers, their dimension and the formation of defects remains a technological challenge.…”
Section: Introductionmentioning
confidence: 99%
“…h‐BN can be formed in a large variety of different nanostructures from 3D to 0D, such as monolayers, nanoribbons, nanotubes, nanodots, nanocages, and fullerene‐like molecules. [ 7,8 ] In particular, h‐BN can be easily exfoliated from bulk crystals down to few layers or deposited as monolayer using different methods. [ 9 ] h‐BN nanosheets have been obtained by developing both top‐down and bottom‐up routes even if controlling the number of layers, their dimension and the formation of defects remains a technological challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Oxidation or hydroxylation of h‐BN in air has been reported. [ 20,23–26 ] Li et al found that oxidation of h‐BN occurred at 850°C. [ 25 ] Even though the thermodynamic reaction temperature between h‐BN and oxygen is above 800°C, oxidation of h‐BN at 600°C has been reported due to some defects on the surface of h‐BN during the initial stage of oxidation.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it has been reported that the covalent functionalization of BNNSs can be performed based on an oxidation tactic that produces several defect sites, which was carried out via direct functionalization at chemical interfaces. [169][170][171][172] However, although this tactic is capable of obtaining extremely stable dispersions of BNNSs, the creation of numerous defect sites on BNNSs due to vigorous oxidation results in reduced lateral sizes and the degradation of the inherent performance of BNNSs. 173,174 Earlier, He, Holzinger et al demonstrated the covalent functionalization of graphene and CNTs using nitrene chemistry.…”
Section: Covalent Surface Functionalization Of Bnnss/bnntsmentioning
confidence: 99%